ECO-MORPHOLOGICAL DIFFERENTIATION OF TILAPIA SPECIES IN SELECTED RESERVOIRS OF KANO STATE, NIGERIA: Morphometric variation among and within Tilapia species of different reservoirs in Kano State - Abdul-Azeez, Hassan (Nigerian Journal of Fisheries, 2025)
Morphological differentiation among intra-specific fish populations often depicts their living conditions directly influenced by differences in their environmental conditions. This study evaluates the eco-morphological differentiation of three commercially significant cichlids (Oreochromis niloticus, Sarotherodon galilaeus, and Coptodon zillii) across five heterogeneous reservoirs (Kanye, Tiga, Thomas, Bagwai, and Pada) in Kano State, Nigeria. Morphometric data from 270 fish specimens (n=30 per population) were characterized using thirteen body traits to assess phenotypic plasticity. Results indicated distinct habitat-induced size structuring: O. niloticus in the large Tiga and Kanye reservoirs displayed robust growth forms (i.e., mean Total Length 18.2–19.2 cm, Body Depth 6.09-6.22cm), whereas S. galilaeus in the smaller Thomas Reservoir exhibited significant (P<0.05) stunting growth (mean TL 10.7 cm, Body Depth 3.90cm ), a possible indication of life-history trade-offs driven by spatial limitation and potential fisheries-induced evolution. Following allometric adjustment, Multivariate Analysis of Variance (MANOVA) and Linear Discriminant Analysis (LDA) confirmed significant population divergence (P < 0.05). Key discriminatory traits included Caudal Peduncle Depth (CPD), Body Depth (BD), and Head Length (HL), reflecting possible functional adaptations to ecological imbalance, and trophic niches. The observed phenotypic patterns clearly demonstrate that the reservoir populations function as distinct management units. These findings advocate for site-specific conservation strategies that takes into account for the local stock health and evolutionary pressure